A retrospective study on analyzing the role of oocyte maturation arrest as a causative factor for infertility in unexplained infertility - S., Mahalakshmi; Lokeshwari, J.; Sharma, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Birth is often referred to as “the miracle of life” and very rightly so since successful pregnancy represents a complex, a highly coordinated succession of biological processes. In this regard, it is remarkable that pregnancy ever occurs at all. Infertility is a reproductive system disorder affecting 10.7% to 15.5% of couples. Highly heterogeneous in etiology. Investigating the cause is necessary for guiding treatment options. Aim of the study was to determine the percentage of immature oocytes retrieved at the metaphase 1 stage and germinal vesicle stage and its outcome. Methods: Total 30 cases were included for this retrospective analysis of data done at ARC fertility center, Saveetha Medical College. This study analyzed the data of patients with unexplained infertility who underwent ICSI centers (affiliated to Saveetha University) meeting inclusion criteria and willing to participate in the study. Results: The mean number of fertilized oocytes among those with more than 25% immature oocyte proportion was 1.18 while among those with less than 25% immature oocyte proportion was 4.13. The chance of fertilization of the oocyte increases when the percentage of immature oocyte was less than or equal to 25%. The association was found to be statistically significant with p-value <0.05. Conclusions: Thus, some intrinsic oocyte factor could be involved in causing maturation arrest in such couples and resulting in multiple failed IVF cycles.so this oocyte factor could be a major cause in many cases of unexplained infertility.